The haunting of Gabriel Ashe - Poblocki, Dan (Scholastic Press, 2013)
Since eighth-grader Gabriel Ashe moved into his grandmother's house he has been spending a lot of time playing in the woods with his new friend Seth, but the games Seth invents involve a child-eating monster called the Hunter, and Gabriel is not sure how much is imagination and how much real.